1990
DOI: 10.1063/1.859280
|View full text |Cite
|
Sign up to set email alerts
|

Analytic solutions and particle simulations of cross-field plasma sheaths

Abstract: Particle simulations have been made of an infinite plasma slab, bounded by absorbing conducting walls, with a magnetic field parallel to the walls. The simulations have been either one dimensional or two dimensional, with the magnetic field normal to the simulation plane. Initially, the plasma has a uniform density between the walls and there is a uniform source of ions and electrons to replace particles lost to the walls. In the one-dimensional (1-D) case, there is no diffusion of the particle guiding centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…that can be injected in Eq. (21). After integration between the Chodura sheath entrance and the plasma center, it comes that φ c − φ(0) = −0.5T e , which is independent of the magnetic field incidence.…”
Section: Tementioning
confidence: 92%
See 1 more Smart Citation
“…that can be injected in Eq. (21). After integration between the Chodura sheath entrance and the plasma center, it comes that φ c − φ(0) = −0.5T e , which is independent of the magnetic field incidence.…”
Section: Tementioning
confidence: 92%
“…Note that in the limit of θ → 0, in a 1d/3V description of the plasma, the particle flux at the wall is expected to cancel in the collisionless limit because particles can not drift perpendicular to the field line. Some authors have addressed this quasi-static issue theoretically and by using particle-in-cell (PIC) simulations [17][18][19][20][21][22][23][24] . They showed that the potential drop at the vicinity of the surface is opposite, ie.…”
Section: Introductionmentioning
confidence: 99%
“…Theilhaber and Birdsall showed in the context of bi-dimensional PIC simulations that Kelvin-Helmholtz instability due to the velocity shear within the sheath allows a particles drift across the magnetic field lines. They evidenced that the potential drop within the sheath keeps a positive value and that the sheath extent reaches 5R l [17][18][19] . When collisions are taken into account, both ions and electrons diffuse through the field line at a different rate.…”
Section: Introductionmentioning
confidence: 99%
“…In further studies, authors faced the impossibility of solving the Poisson equation from a kinetic theory and used numerical calculations to derive scaling laws. They found that s scales with R L /λ d and a ∆φ of the order of the ion temperature 12,[15][16][17] , but no simple expression connecting s, or ∆φ, with the plasma parameters such as the ion and electron temperature and mass (T i , T e , m i and m e resp. ), or with B, has ever been derived.…”
Section: Introductionmentioning
confidence: 99%